Предмет: Алгебра,
автор: apdvorakovska
упростить выражение 1/(n+1)!-1/(n+2)!
Ответы
Автор ответа:
3
1/(n+1)!-1/(n+1)!*(n+2)=(n+2-1)/(n+1)!(n+2)=(n+1)/n!(n+1)(n+2)=1/n!*(n+2)
Автор ответа:
6
1/(n+1) - 1/(n+2) = (n+2) - (n+1) / (n+1) * (n+2) = n+2-n-1 / (n+1) * (n+2) = 1 / (n+1) * (n+2)
Похожие вопросы
Предмет: Окружающий мир,
автор: SonechkaGrishina
Предмет: Русский язык,
автор: Angelina089
Предмет: Русский язык,
автор: matveev85
Предмет: Русский язык,
автор: tixonovanata
Предмет: Русский язык,
автор: 2285109